2018
DOI: 10.1002/cpp.2328
|View full text |Cite|
|
Sign up to set email alerts
|

Burnout amongst clinical and counselling psychologist: The role of early maladaptive schemas and coping modes as vulnerability factors

Abstract: Psychologists are subject to multiple competing emotional demands that increase the risk of burnout. Research has demonstrated that burnout arises from both organizational and personal factors, including psychologists' personal beliefs and coping. Preliminary research indicates that early maladaptive schemas (EMS) are associated with high burnout, yet, to date, the role of EMS and associated coping responses (maladaptive coping modes [MCM]) in predicting high burnout amongst psychologists has not been investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 86 publications
(122 reference statements)
2
63
0
11
Order By: Relevance
“…Such findings contribute to the existing literature by providing reasons for why custodial teachers encounter a high prevalence of burnout and distress. Our results are consistent with previous findings [47,48]. The former authors showed that the unrelenting standards schema is a predictor of burnout, whereas the latter authors argued that professionals who experience difficulties in setting boundaries with their clients experience a higher level of burnout.…”
Section: Discussionsupporting
confidence: 93%
“…Such findings contribute to the existing literature by providing reasons for why custodial teachers encounter a high prevalence of burnout and distress. Our results are consistent with previous findings [47,48]. The former authors showed that the unrelenting standards schema is a predictor of burnout, whereas the latter authors argued that professionals who experience difficulties in setting boundaries with their clients experience a higher level of burnout.…”
Section: Discussionsupporting
confidence: 93%
“…Interesting results obtained by Simpson et al in a study performed in clinical psychologists, which is a group with high risk of burnout. 43 The results indicated that early maladaptive schemas and specific coping modes could predict burnout syndrome. In conclusion, the results obtained indicate different levels of job-related stress associated with different sources in bank employees working in managerial and non-managerial positions.…”
mentioning
confidence: 94%
“…Intrinsic factors are of great importance to develop preventive and support measures for stressed physicians/PT. (Simpson et al 2019) oder im Zusammenhang mit den Folgen beruflichen Stresses, wie Burn-out (Kaeding et al 2017;Khorshidian et al 2017).…”
Section: Discussionunclassified